High Hole Mobility and Low Leakage Thin-Body (In)GaSb p-MOSFETs Grown on High-Bandgap AlGaSb - Sang-Hyeon Kim (IEEE, 2021)
In this study, we demonstrated low leakage current and high mobility thin body (In)GaSb p-FETs. Through the optimization of the V/III ratio during the epitaxial growth, we achieved a highly insulating bottom Al0.95Ga0.05Sb barrier, which eliminates the junction leakage. We also suppressed the interface trap-assisted surface leakage current by introducing In0.53Ga0.47As surface passivation on the GaSb channel. Furthermore, GaSb/InGaSb/GaSb quantum well (QW) channel structure provided significant improvement in effective mobility ( ${μ }_{ eff}$ ) characteristics. As a result, the fabricated devices showed the lowest off-leakage current ( ${I} _{ off}$ ), subthreshold slope ( ${S}$ . ${S}$ .) and high $μ _{ eff}$ among reported GaSb p-MOSFETs.